Longitudinal nasal meticillin-resistant Staphylococcus aureus colonization among resident physicians at an urban, public hospital - Carnell, Jennifer; Hern, Gene; Singh, Amandeep; Lambert, Larry; Cheung, Paul; Cisse, Bitou; Silver, Charlotte; Frazee, Bradley (International Journal of Infection Control, 2011)
Little is known about longitudinal meticillin-resistant Staphylococcus aureus (MRSA) colonization rates in resident physicians, specifically. This three-year study examined Staphylococcus aureus (S. aureus) nasal colonization in resident physicians, the proportion due to MRSA, the relationship with number of years in training, and longitudinal trends in colonization. Nasal swabs were collected annually (2006-2008) from a convenience sample of resident physicians at an urban, public hospital in Oakland, California, U.S.A. Swabs underwent culture and sensitivity testing, including selective MRSA culture. A total of 441 samples were obtained from 262 individuals. Overall, S. aureus was detected in 13 residents (5.0%), MRSA in 8 (3.1%), and methicillin-sensitive Staphylococcus aureus (MSSA) in 5 (1.9%). The proportion of resident physicians with MRSA nasal colonization was 2.0%, 2.7%, and 2.0% in 2006, 2007, and 2008, respectively. As the total number of years in training increased (from 1 to 5), MRSA nasal colonization steadily increased from 1.2% to 8.7% in resident physicians. Overall S. aureus nasal colonization was low, MRSA colonization exceeded MSSA colonization, and colonization was dynamic in individuals. MRSA colonization steadily increased as residents progressed through training suggesting that duration of time in patient care is a risk factor for colonization.